Academic writing conventions in Czech English-medium linguistics journals : Continuity and change over the last 30 years - Dontcheva-Navratilova, Olga (Jan Kochanowski University Press, 2023)
This paper studies the development of academic writing conventions in Englishmedium research articles (RAs) by Czech linguists published in two national journals (Brno Studies in English and Linguistica Pragensia) over the last 30 years. Drawing on the genre analysis framework, the study investigates possible changes in the titles, rhetorical structure, statement of aims, research questions and hypotheses, and personal and locational metadiscourse markers for writer and reader reference in a small corpus of 20 RAs. The comparative diachronic analysis aims to identify continuity and change in the evolution of academic writing conventions and the factors influencing them. The findings indicate that Czech English-medium RAs have gradually adopted a more transparent rhetorical structure close to the IMRAD model, their titles have gained in informativeness, and researcher visibility has been enhanced due to an increase in locational and exclusive personal self-mention. These tendencies point to hybridity in the present-day English-medium discourse of Czech linguists which stems from the adaptation of diverging academic writing traditions to meet the publication needs of the authors.